UP TO DAY POSSIBILITIES OF ATRIAL FIBRILLATION PREVENTION - E. A. Protasova; N. V. Furman; O. V. Reshet'ko (Столичная издательская компания, 2015)
Inhibitors of the renin-angiotensin-aldosterone system, statins, and possibly , ω-3 polyunsaturated fatty acids may influence the incidence of atrial fibrillation (AF), and can be used to prevent it. In recent medical literature, this approach is referred to as upstream treatment. The results of experiments and clinical studies show that the use of these drugs may be useful for AF primary prevention in certain categories of patients. Nevertheless, there are currently no sufficient evidences to justify these recommendations and apply them to a wider range of patients with AF risk factors. Thus, it is reasonable to continue studies on both primary and secondary AF prevention.